2021
DOI: 10.1177/20503121211054373
|View full text |Cite
|
Sign up to set email alerts
|

Plastic and aesthetic surgery among medical students: A cross-sectional study

Abstract: Objectives: The wide variety of operations that a plastic surgeon can deal with creates confusion regarding its proper scope. This confusion was observed in primary physicians as well as medical students. Increasing the perception of medical students toward plastic surgery can aid in career decision-making and early referral patterns. The aim of this study is to gauge a holistic overview of how medical students and interns perceive the plastic and aesthetic surgical specialty in King Faisal University and to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…10 Similar results were found in a 2021 study where medical students did not associate plastic surgery with hand surgery and peripheral neuropathies. 11 Evidence supporting this hypothesis was published in a 2017 study that found television portrayals significantly influenced medical students' understanding of plastic surgery. 12 All these disparities may be linked to a lack of early exposure in medical school and increased reliance on societal stereotypes in forming perceptions of plastic surgery.…”
mentioning
confidence: 94%
See 2 more Smart Citations
“…10 Similar results were found in a 2021 study where medical students did not associate plastic surgery with hand surgery and peripheral neuropathies. 11 Evidence supporting this hypothesis was published in a 2017 study that found television portrayals significantly influenced medical students' understanding of plastic surgery. 12 All these disparities may be linked to a lack of early exposure in medical school and increased reliance on societal stereotypes in forming perceptions of plastic surgery.…”
mentioning
confidence: 94%
“…12 All these disparities may be linked to a lack of early exposure in medical school and increased reliance on societal stereotypes in forming perceptions of plastic surgery. 10–12…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…3,4 Medical students specifically have demonstrated a limited understanding of the breadth of plastic surgery. [5][6][7][8] This is largely due to limited exposure to the field throughout medical education, leaving students to draw upon external sources such as social media.…”
Section: Introductionmentioning
confidence: 99%